Sustainable HR Development Strategy on Local Potential in Klaisu Village Jayapura Regency - Risamasu, Ferdinand; Srem, Ade Irma A.; Siwa, Siane F.; Wabe, Tiara G.; Rumbiak, Yensawai E.; Najima, Najima (International Journal of Economics Development Research (IJEDR), 2025)
Community-based tourism development in Indonesia, especially in villages that have great natural and cultural potential, still faces challenges in increasing community participation and sustainable management. This study aims to analyse sustainable human resource development strategies in tourism objects in Klaisu Village, Jayapura Regency. This research uses a qualitative approach with a purposive sampling method to select 11 informants who are community leaders of Klaisu Village, who have direct experience in tourism and natural resource management. Data were collected through in-depth interviews, field observations, and documentation analysis. The results showed that although Klaisu Village has great tourism potential, such as agricultural products and natural beauty, community participation in tourism management is still low. Sustainable human resource development through training and community empowerment, as well as collaboration with external parties, are the main keys in overcoming this challenge. In addition, marketing issues, financial issues, and social issues are also inhibiting factors in the management of sustainable tourism destinations. The implication of this research is the need to increase community capacity in tourism management and strengthen cooperation with various parties to realise economic, social and cultural sustainability in Klaisu Village.